Jigsaw Type Cooperative Learning Model to Improve Student Learning Outcomes on Various Work Themes in Class IV State Primary School 064986 Medan Amplas - Nurul Annisa; Nurmaidina (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the effectiveness of the Jigsaw cooperative learning model to improve student learning outcomes in thematic learning theme 4